Analisis Penerapan Multimedia Interaktif di Kelas 5 SDN Karundang 1 - Pribadi, Reksa Adya; Hosi’ah, Hosi’ah; Siahaan, Anggel Veronika; Afrizal, Muhamad; Fajaryna, Gusty Ekka (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research was purposed to analyze the application of interactive multimedia in grade 5 at SDN Karundang 1. This research uses a qualitative approach with naturalistic research methods. The subject in this study are students in the fifth grade. The technique used to conduct this research is observation and documentation. The results of this study show that the use of interactive multimedia in learning activities can improve the activity of students because the media contains interesting appearances such as animations and games. So it can be concluded that the application of interactive multimedia in class 5 at SDN Karundang 1 can increase the activity during learning activities.